SECOND JAIPURITE FIND IN THE WORLD - Gertsen L.Y.; Kotel'nikov P.Y.; Yeremeyeva Y.Y. (My University, 1988)
Jaipurite, cobalt sulfide CoS, was discovered in 1846 and named for the locality in India, where it was associated with pyrrhotite in old schist. We found jaipurite among minerals of the potassic feldspar-quartz-bornite-chalcopyrite association of the alkalic first stage in the Ken'kuduk and Ozernoye porphyry-copper deposits, central Kazakhstan. This mineral association includes rare carrollite grains, usually crystallized on the contacts between chalcopyrite and gangue minerals and, at Ken'kuduk, contains compled bismuth sulfosalts as well.